Eutectic dual-phase microstructure modulated porous high-entropy alloys as high-performance bifunctional electrocatalysts for water splitting. Issue 20 (3rd May 2022) - Han, Xiao; Chen, Qiao; Chen, Qingxi; Wu, Qingfeng; Xu, Ziyuan; Zheng, Tao; Li, Weizhao; Cui, Dingcong; Duan, Zhiyao; Zhang, Jing; Li, Junjie; Li, Hejun; et al.
Abstract : High entropy alloys (HEAs) are promising as multifunctional electrocatalysts owing to their inherent compositional and structural complexity and thus the multiple active sites for different reactions. Abstract : High entropy alloys (HEAs) are promising as multifunctional electrocatalysts owing to their inherent compositional and structural complexity and thus the multiple active sites for different reactions. Herein, a binder-free bifunctional porous HEA electrode has been designed and fabricated by selectively etching eutectic dual-phase microstructures. The AlCrFeCoNiW HEA consisting of FCC and ordered BCC phases was dealloyed with the aluminum-enriched BCC phase being removed effectively to construct a three-dimensional porous architecture. The porous HEA electrode exhibits excellent hydrogen evolution reaction activity (overpotential of 101 mV at a current density of 10 mA cm −2 ) and oxygen evolution reaction activity (overpotential of 270 mV at a current density of 50 mA cm −2 ), along with outstanding stability under industrial conditions. The in situ electrochemical infrared spectra illustrate that the great electrocatalytic performance in alkaline electrolyte may be closely related to the enhanced interactions between the electrode surface and adsorbed water molecules. First-principles calculations based on density functional theory reveal an improvement in the intrinsic catalytic activity after the dealloying process. This work combines the concept of HEA with multiple active sites for catalysis and selective etching tuned by the eutectic microstructure, paving a new way for designing low-cost self-supporting electrodes for future sustainable energy applications.